Antagonistic Interaction of Staphylococcus aureus Toward Candida glabrata During in vitro Biofilm Formation Is Caused by an Apoptotic Mechanism - Camarillo-Márquez, Omar; Córdova-Alcántara, Itzel M.; Hernández-Rodríguez, Cesar H.; García-Pérez, Blanca E.; Martínez-Rivera, María A.; Rodríguez-Tovar, Aida V. (Frontiers in Microbiology, 2018)
BACKGROUND. Infections caused by Candida species and Staphylococcus aureus are associated with biofilm formation. C. albicans-S. aureus interactions are synergistic due to the significant increase in mixed biofilms and improved resistance to vancomycin of S. aureus. C. glabrata and S. aureus both are nosocomial pathogens that cause opportunistic infections in similar host niches. However, there is scarce information concerning the interaction between these last microorganisms. RESULTS. The relationship between C. glabrata and S. aureus was evaluated by estimating the viability of both microorganisms in co-culture of planktonic cells and in single and mixed biofilms. An antagonistic behavior of S. aureus and their cell-free bacterial supernatant (CFBS) toward C. glabrata, both in planktonic form and in biofilms, was demonstrated. Scanning electron microscopy (SEM), transmission electron microscopy (TEM) and confocal laser scanning microscopy (CLSM) images showed yeast cells surrounded by bacteria, alterations in intracytoplasmic membranes, and non-viable blastoconidia with intact cell walls. Concomitantly, S. aureus cells remained viable and unaltered. The antagonistic activity of S. aureus toward C. glabrata was not due to cell-to-cell contact but the presence of CFBS, which causes a significant decrement in yeast viability and the formation of numerous lipid droplets (LDs), reactive oxygen species (ROS) accumulation, as well as nuclear alterations, and DNA fragmentation indicating the induction of an apoptotic mechanism. CONCLUSION. Our results suggesting the presence of an unknown compound(s) in the S. aureus CFBS that causes cell death in C. glabrata by an apoptotic mechanism.